2021
DOI: 10.53730/ijhs.v5n3.2490
|View full text |Cite
|
Sign up to set email alerts
|

Academic mobility development among university students during COVID-19 pandemic

Abstract: The aim of the article is to study the academic mobility of students in the context of internationalization of education, exchange of experiences and gaining additional knowledge and skills between participants in the process of academic mobility. The research methodology is to use methods of questionnaires, surveys, interviews among students to study the prospects, advantages, disadvantages and opportunities of academic mobility. The results of the study cover the internal and external mobility of university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At the 1st stage of the experiment, during the implementation of the blended learning principles, the research team identified changes in the structure and content of the learning process, highlighting several characteristics (Slipchuk et al, 2021). After adopting the curriculum and teaching materials, several pieces of training from specialists-technicians for all respondents on the necessary technical knowledge for video conferencing, classes on educational platforms, participation in non-formal education, and scientific activities and training initiatives (Candarli & Yuksel, 2012;Viswanathan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…At the 1st stage of the experiment, during the implementation of the blended learning principles, the research team identified changes in the structure and content of the learning process, highlighting several characteristics (Slipchuk et al, 2021). After adopting the curriculum and teaching materials, several pieces of training from specialists-technicians for all respondents on the necessary technical knowledge for video conferencing, classes on educational platforms, participation in non-formal education, and scientific activities and training initiatives (Candarli & Yuksel, 2012;Viswanathan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Financial and legal aid on the part of government agencies and large corporations is important to support these initiatives, as well as the willingness of teachers to promote online education and students -to promote educational motivation. Modern vocational education poses new challenges to the domestic higher education system (Slipchuk et al, 2021). In connection with the economic and social-cultural integration of European and international society, the development of market relations, the increasing complexity of the structure of the current social-economic situation in the context of the COVID-19 pandemic, there is a growing need to train specialists capable of more responsible and competent professionalism (Downar et al, 2010;Vecchio et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These include time costs (during the 2 nd semesters), change of opinion of respondents, and inability to conduct large-scale qualitative research. In the first stage of the study, the research team identified the main characteristics that needed to be investigated to determine the impact of blended learning on education (Slipchuk et al, 2021). First, the changes in curricula that were implemented for the study of humanities disciplines were investigated.…”
Section: Methodsmentioning
confidence: 99%